The role of the source versus the collisionality in predicting a reactor density profile as observed on ASDEX Upgrade discharges. (13th June 2019) - Fable, E.; Angioni, C.; Bobkov, V.; Stober, J.; Bilato, R.; Conway, G.D.; Goerler, T.; McDermott, R.M.; Puetterich, T.; Siccinio, M.; Suttrop, W.; Teschke, M.; et al.
Abstract: The design and optimization of a future tokamak fusion reactor, from the point of view of the plasma performance and output fusion power, requires the understanding of the underlying physics and the validation on present experiments of the theory-based tools used for the predictions. Present experimental efforts are devoted to approach reactor-relevant parameters (collisionality, , normalized heat fluxes and sources, temperatures ratio) as much as possible. In this work a series of discharges performed on ASDEX Upgrade are presented, where plasma density and auxiliary power levels are scanned to cover a parameter space that moves towards reactor relevant parameters. On this dedicated discharge dataset, a first-principle-based model is then applied for validation. The degree of agreement between code results and experimental measurements is shown and discussed. In cases where discrepancy is found, possible causes are identified. It is shown that the employed modeling tool can predict the overall trend, consistent with more fundamental theoretical considerations, although quantitative extrapolation still has to be performed with care. Key results of this work show that the density peaking is mainly sustained by turbulence, with a minor role for the fueling source, and how this experimental demonstration is important to predict future reactor density profiles. Moreover, the role of electromagnetic effects is also pointed out.